Modelling and performance evaluation of PV controller in various reference frame - Pushpa, K. R.; Geetha, R. S. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Many closed-loop automations of grid-connected and standalone inverters use controllers for various process control. The performance of the voltage source inverter (VSI) used in such applications depends on the characteristics of the controller. The gating pulses for the inverter are generated based on controller output and it affects the overall performance of the system. In this regard, the design and performance analysis of the controllers becomes an important integral part of any system under consideration. There are various methods available to design a controller. This paper discusses the design, modeling, and performance of a PI controller for single-phase VSI in stationary and rotating reference frames which helps in selecting a controller for the specific system configuration. The dynamic behavior of the controller with respect to the above reference frames and its effects on VSI output when subjected to load disturbance is evaluated. The controller design is carried out with two different current control strategies namely inductor current and capacitor current sensing. The stability of the system with the designed controller is analyzed and the results are compared.